Enhanced optical properties and mechanisms of Ba-doped LaMnO3 perovskite ceramic coating. Issue 7 (1st April 2023) - Yu, Liuxu; Wang, Mingyuan; Hou, Haigang; Zhang, Xiangzhao; Lei, Shuangying; Liu, Junlin; Liu, Guiwu; Qiao, Guanjun
Abstract: Although doped LaCrO3 perovskite oxides present excellent optical absorption properties, it is inevitable that the toxic Cr ions can cause serious environmental pollution. Herein, we reported a series of A-site doped LaMnO3 -based perovskite bulks and porous coatings, and the relationship between microstructure and optical absorption properties of LaMnO3 -based coatings and the light absorption enhancement mechanisms were mainly investigated and analyzed. The La0 · 5 Ba0 · 7 MnO3 coating sample possesses the highest average absorptivities of 94.07% and 88.87% in the visible region and in the wavelength range of 0.2–20 μm, respectively, and the La0 · 5 Ba0 · 7 MnO3 -coated Al2 O3 crucible has more superior photothermal conversion performance than the uncoated and LaMnO3 -coated Al2 O3 crucibles under solar and infrared radiations. Experimental results and first-principles calculations indicate that the doping of Ba can increase the free carrier concentration, effectively enhance the interactions between photons and carriers, and thus improve the light absorption in the visible and near-infrared regions. Meanwhile, the increase of porosity and the decreases of grain size and bandgap can contribute to the light absorption enhancement. This work provides a promising candidate as coating materials for high-temperature photothermal conversion.